Gender differences in financial knowledge overconfidence among older adults. (20th October 2021) - Kim, Kyoung Tae; Lee, Sunwoo; Kim, Hohyun
Abstract: This study explores gender differences in financial knowledge overconfidence among older adults using the 2016 Health and Retirement Study. We find that older females have relatively lower objective financial knowledge than do older males, while they evaluate themselves to be as financially knowledgeable as older males. Further, several measures of overconfidence in financial knowledge are higher in older females than older males. A number of robustness checks, including a propensity score matching method, use of a polygenic risk scores, and a test of reproduction using the Survey of Consumer Finances corroborate these gender differences. Results from decomposition analyses of overconfidence indices show that relatively lower crystallized intelligence of older females is one of the main reasons that widens the gender gap among older adults. Lower likelihoods of attaining a college education degree and being in a relationship are additional contributing factors that explain the gender gap. This study provides insights into understanding the gender gap in financial knowledge and its implications for government education or intervention programs to support older adults' wellbeing in retirement.